(untitled) (Research, Society and Development, 2022)
The objective of this study was to analyze the competences interpreted as relevant by the preceptors who work in the context of the Family Health Strategy. A research was developed using quantitative and qualitative data, collected from medical and nursing professionals who act as preceptors of students of the medical course of a Higher Education Institution. The main competences identified as necessary for the activity of preceptorship are related to the integration of theory and practice, the improvement of the critical-reflexive reasoning of the student, through assessments, constructive and proficient feedbacks. It was identified that a significant portion of the preceptors did not undergo specific training for the development of this activity. This training gap is positioned as an important element to be overcome by Higher Education Institutions that send their students to practical activity, with the collaboration of a preceptor. The provision of training for the preceptor would provide the establishment of standards of conduct to carry out the activity of evaluation and improvement of the teaching and learning system of medical students.